Effects of Remote Work Policies on Employee Job Satisfaction in Burundi - Ntihirageza, Phillip (European Journal of Human Resource, 2024)
Purpose: The aim of the study was to assess the effects of remote work policies on employee job satisfaction in Burundi. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that remote work can enhance job satisfaction by providing employees with greater flexibility and autonomy, allowing them to better balance their work and personal lives. This flexibility often leads to reduced stress levels and increased overall well-being, contributing to a more positive work experience. Furthermore, the elimination of commuting time and costs, coupled with the ability to create a personalized and comfortable working environment, further enhances job satisfaction. However, these benefits are not universal; some employees may experience feelings of isolation and a lack of camaraderie with colleagues, which can negatively affect job satisfaction. Effective communication and support from management are crucial in mitigating these challenges. Overall, while remote work policies generally tend to improve job satisfaction by offering flexibility and work-life balance, they must be implemented thoughtfully to address potential drawbacks related to social interaction and team cohesion. Implications to Theory, Practice and Policy: Job characteristics theory, self-determination theory and social exchange theory may be used to anchor future studies on assessing the effects of remote work policies on employee job satisfaction in Burundi. Organizations should develop flexible remote work policies tailored to individual employee needs. Incorporate mental health support into remote work policies. Organizations should provide access to mental health services and promote a culture of well-being to reduce burnout and improve job satisfaction. Develop policies that foster a strong, inclusive organizational culture even in remote settings.